Back-to-basics audio - Nathan, Julian (Newnes, 1998)
Back to Basics Audio is a thorough, yet approachable handbook on audio electronics theory and equipment. The first part of the book discusses electrical and audio principles. Those principles form a basis for understanding the operation of equipment and systems, covered in the second section. Finally, the author addresses planning and installation of a home audio system. Notes on home theater systems, speaker placement and calibration System planning, diagram analysis, and signal processing Easy introduction to practical audio, acoustics, and electrical theory.